Applicability and benefits of dance therapy as a health care practice: an integrative review (Research, Society and Development, 2020)
The objective of this work was to evaluate the applicability and the benefits of dance therapy as a health care practice. This is an integrative literature review, developed in the first half of 2019, on the databases Latin American and Caribbean Health Sciences Literature (Lilacs), Nursing Database (BDENF) and Scientific Electronic Library Online (SciELO), combining the descriptors: dance and therapy. The thematic analysis was organized in three categories: Folk Dance, Ballroom Dance and Free Dance. The results show that the practice provides an improvement in motor aspects, in self-esteem and in functional independence, and helps individuals to be participatory and active in the community. It constitutes a physical activity, being recommended for reducing risk factors for cardiovascular diseases and disorders. The dance configures as a therapeutic way able to contemplate the human being in all his/her needs and oddities, allowing connection between mind and body, providing the individual perceptions about health and quality of life.